Penerapan Model Kooperatif Tipe Team Assisted Individualization (TAI) pada Pembelajaran Matematika - Rahmayanti, Dita; Friansah, Drajat; Yuneti, Armi (Jurnal Pendidikan Matematika : Judika Education, 2023)
The aim of this research is to determine the completeness of the mathematics learning outcomes of fifth grade students at SD Negeri 17 Lubuklinggau after implementing the Team Assisted Individualization (TAI) type cooperative model. This type of research is quasi-experimental research carried out without a comparison class with a pre-test and post-test group design. The population is class V of SD Negeri 17 Lubuklinggau for the 2022-2023 academic year, which consists of 17 students. Data collection was taken using test techniques. The collected data was analyzed using the t-test. Based on the results of the t-test analysis at the significance level α = 0.05, it is obtained (2.600) > (1.75). In conclusion, the mathematics learning outcomes of fifth grade students at SD Negeri 17 Lubuklinggau after implementing the Team Assisted Individualization (TAI) type cooperative model were significantly complete. Keywords: Cooperative Model, Team Assisted Individualization (TAI), Mathematics Learning